IMPLEMENTATION OF SCRUM FRAMEWORK IN AGILE TECHNOLOGY IN GUEST RECEPTION OF GOVERNMENT OFFICES: MONITORING OF GUEST RECEPTION DASHBOARD - Maulana, Hanif; Mahdiana, Deni (JIPI (Jurnal Ilmiah Penelitian dan Pembelajaran Informatika), 2025)
The presence of guests from various circles at the Prosecutor's Office is very diverse, so guest data collection is needed to monitor guests who come to the prosecutor's office. Data collection is carried out by adding several features to the dashboard according to the year, including the number  of guests  and guest  graphs of various types,  including, the average number of visit duration, the overall number of visits, the number of registered guests, the number of vehicles entering, the number of PTSP visits, the number of ticket taking, the visit graph, the guest type graph, the guest type graph, the visit type graph, the guest age graph, the guest arrival time graph, the time of arrival at the kamdal,  graph of the time of guests coming to PTSP, graph of total visits by day, graph of total visits by month, graph of the most visitors received, graph of total survey votes, and graph  of most frequently  visited guest data. The method used is development  by implementing  the Scrum Framework, one of the Agile development methodologies. The stages carried out consist of, problem identification, literature study, product backlog and sprint planning, sprint backlog, daily scrum, as well as sprint review and restrospective sprints. The duration of the work time for this project is estimated at 39 working days. The final results  obtained from  this research are in the form of details of the work and scheduling, to the prototype of the interface.